Potential of extravasated platelet aggregation as a surrogate marker for overall survival in patients with advanced gastric cancer treated with preoperative docetaxel, cisplatin and S-1: a retrospective observational study - Saito, Hiroto (BMC Cancer, 2017)
BACKGROUND: The theory of extravasated platelet aggregation in cancer lesions was recently introduced. We investigated the association of platelet aggregation in gastric cancer stroma with clinicopathological features, chemotherapeutic response, pathological response, and survival. METHODS: The study comprised 78 patients with advanced gastric cancer who had undergone gastrectomy with or without combination of docetaxel, cisplatin and S-1 (DCS) as preoperative chemotherapy between 2005 and 2014. The patients were divided into two groups: patients who had received preoperative DCS therapy forming the p-DCS group and patients who had not received preoperative DCS therapy forming the control group. The 39 patients in the control group had received gastrectomy and postoperative chemotherapy of S-1 alone. Platelet aggregation in biopsy specimens before preoperative DCS therapy in the p-DCS group and at the time of diagnosis in the control group were evaluated using CD42b immunohistochemical staining. RESULTS: Twenty-four patients in the p-DCS group and 19 in the control group were found to have platelet aggregation in their cancer stroma. Patients with histologically confirmed platelet aggregation had significantly higher rates of chemoresistance (58.3%) than those without platelet aggregation (20.0%) (P = 0.019). According to multivariate analysis, CD42b expression (odds ratio: 5.102, 95% confidence interval: 1.039–25.00, P = 0.045) was correlated with chemoresistance. CD42b expression and histological non-responder status were both significantly correlated with poor overall survival (OS) (P = 0.012, P = 0.016); however, RECIST was not correlated with OS. In the control group, CD42b expression was also significantly correlated with poor overall survival (OS) (P = 0.033). In the p-DCS group, according to multivariate analysis, male sex (hazard ratio: 0.281, 95% confidence interval: 0.093–0.846, P = 0.024) was correlated with good prognosis and CD42b expression (hazard ratio: 4.406, 95% confidence interval: 1.325–14.65, P = 0.016) with poor prognosis. CONCLUSIONS: This study suggests that platelets in gastric cancer stroma may create a favorable microenvironment for chemoresistance. CD42b immunohistochemical staining of biopsy specimens is a promising candidate for being a prognostic marker in patients with gastric cancer.